Impact of waste management practices on the perceived quality of life of people living in Barangay 422, Sampaloc Manila - Bucag, Rachel Ronica E.; Citron, Mary Joy L.; Cruz, Jocy Marie P.; Flores Jr., Ronilo C.; Lacap, Apple Joy M.; Landicho, Julie Ann R. (Manila : National University, 2023)
Waste management practices have a significant impact on the quality of life in various ways, and their relationships can be multifaceted.
Chapter 1. The Problem -- Chapter 2. Review of related literature -- Chapter 3. Methodology / Materials and Methods -- Chapter 4. Presentation, Analysis and Interpretation of data -- Chapter 5. Summary, Conclusion and Recommendation -- References -- Appendices
Includes bibliographical references.